2005
DOI: 10.1148/radiol.2361040456
|View full text |Cite
|
Sign up to set email alerts
|

Use of Productivity and Financial Indicators for Monitoring Performance in Academic Radiology Departments: U.S. Nationwide Survey

Abstract: Academic radiology departments across the United States do not use a standardized set of productivity and financial indicators to measure departmental performance. Examination volume is the most frequently used productivity indicator, whereas general expenses are commonly used as indicators of financial status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Thus, it can be concluded that the field of imaging is faced with the challenges of increasing service use, declining reimbursements, and staff shortages. In such an economically challenging environment, it becomes crucial for the MIDs to monitor their performance so that they can provide a high quality of services while staying within operational boundaries [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be concluded that the field of imaging is faced with the challenges of increasing service use, declining reimbursements, and staff shortages. In such an economically challenging environment, it becomes crucial for the MIDs to monitor their performance so that they can provide a high quality of services while staying within operational boundaries [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several articles discussing performance metrics of MIDs were identified [8,[10][11][12][13][14][15][16][17][18][19][20][21][22]. All the metrics were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…For customer satisfaction, the most commonly used indicators are patient complaints, patient satisfaction and patient waiting time. Referring physician satisfaction and employee satisfaction were used in less than half of the departments surveyed [11]. For productivity, the most commonly used indicator is examination volume while for financial status, general expenses is most commonly used.…”
Section: Ways To Improve Service Delivery In a Radiology Departmentmentioning
confidence: 99%
“…A number of such scorecards have been described, most of which are, appropriately, centered around image care delivery and patient safety (2,13,14). Important parameters related to imaging care delivery include measures in the areas of safety, patient access, customer satisfaction, appropriateness of examinations, percentage of standard protocols used, and timeliness of reporting (2,13).…”
Section: Introductionmentioning
confidence: 99%